Impact of Cardiovascular Risk Factors on Carotid Intima-Media Thickness and Degree of Severity: A Cross-Sectional Study - Ren, L.; Cai, J.; Liang, J.; Li, W.; Sun, Zhonghua (PUBLIC LIBRARY SCIENCE, 2015)
OBJECTIVE: Age, hypertension, dyslipidemia and diabetes are common cardiovascular risk factors (CVRFs) that contribute to the development of atherosclerosis in cardiovascular system including carotid artery disease. However, the impact of these risk factors on the increased carotid intima-media thickness (cIMT) and degree of carotid severity remains to be further clarified. This study aims to evaluate the relationship between CVRFs and degree of carotid severity and cIMT in high-risk subjects. METHODS: Four thousand and three hundred ninety-four subjects with one or more risk factors were retrospectively reviewed in this study. Patients were divided into different groups based on age, the type and quantity of CVRFs. cIMT and degree of carotid artery stenosis were measured and analyzed based on carotid ultrasound imaging with findings compared to the CVRFs to determine the correlation between these variables. RESULTS: Aging was significantly associated with degree of severity (P < 0.05) and cIMT was significantly increased with age (P < 0.05). Individual CVRF analysis shows that hypertension was more related to the degree of severity than dyslipidemia and diabetes with corresponding abnormal cIMT rates being 79.39%, 72.98% and 32.37%, respectively. The prevalence of carotid atherosclerosis were 20.06%, 22.88% and 28.63%, respectively corresponding to patients with zero, one and more than one chronic diseases. The percentage of abnormal cIMT in hypertensive patient group with dyslipidemia is significantly higher than the other groups (P< 0.05). CONCLUSIONS: This study shows a direct correlation between the degree of carotid severity and cIMT and cardiovascular risk factors, especially with age and hypertension. Carotid atherosclerosis is closely related to the number of cardiovascular risk factors.